Pengaruh Model The Power of Two terhadap Hasil Belajar Peserta Didik pada Mata Pelajaran Fikih Kelas X MAN 1 Padang Pariaman - Nur Sakinah Siregar; Khadijah Khadijah; Ilman Nasution; Azhariah Fatia (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study is motivated by the suboptimal learning outcomes of students in Fiqh for Grade X at MAN 1 Padang Pariaman in the 2025/2026 academic year. The learning process is still dominated by lecture methods, causing students to be less focused and unable to understand and summarize the material effectively. Therefore, an alternative learning model is needed, namely The Power of Two model, which emphasizes collaboration between students in pairs to improve understanding. This study aims to determine student learning outcomes before and after the implementation of The Power of Two model and to analyze its effect on improving learning outcomes. This research uses a quantitative approach with an experimental method and a one-group pretest-posttest design. The population consists of all Grade X students, with the sample selected using purposive sampling, namely class X E7 as the experimental class. Data were collected through pretest and posttest instruments and analyzed using hypothesis testing with SPSS version 20. The results showed that the average pretest score was 68.92, while the posttest average increased to 85.40. Hypothesis testing results indicated a significance value of <0.000 (<0.05), meaning that Ha was accepted and H0 was rejected. Thus, The Power of Two model has a significant and strong effect on improving student learning outcomes in Fiqh subjects for Grade X students at MAN 1 Padang Pariaman.